A simple lattice Boltzmann model for conjugate heat transfer research - Chen, S.; Yan, Y.Y.; Gong, W. (Elsevier, 2017)
In this paper a lattice Boltzmann (LB) model is proposed for conjugated heat transfer research. Through taking the most advantages of the standard LB method, the present model can remedy the shortcomings of the available related LB models via a simple way and meanwhile a number of intrinsic advantages of the standard LB method are preserved. It does not require any specific treatment dependent on interface topology and independent from the choice of lattice model. Moreover, it can be used for unsteady problems with complicated and time dependent interfaces. The accuracy and reliability of the present model are validated by three nontrivial benchmark tests. The good agreements between the present numerical prediction and available open data demonstrate the applicability of the present model for complicated conjugated heat transfer problems. Finally, the present model could be extended to some other important areas straightforwardly, such as fluid–solid phase change modeling.